A preliminary study on occurrence and characterization of extended spectrum beta lactamase producing extra intestinal pathogenic Escherichia coli isolated from dogs - W. A. P. M. Dewasmika (Sri Lankan Journal of Infectious Diseases, 2021)
NAA